Electrolysing mud: Membraneless electrolysis of water for hydrogen production using montmorillonite-rich marine mud - Christina Biggs (Applied Clay Science, 2023)
This paper describes a design for a low-cost membraneless water electrolyser for the production of green hydrogen that used a viscous electrolyte of naturally abundant montmorillonite-rich marine mud in a DEFT (divergent electrode flow through) geometry with stainless steel (304) mesh electrodes. The ratio of smectite to non-swelling clays in the mud was 1:2. The electrolyte was prepared by resuspending the mud in tap-water to remove the salt, and NaOH 1 M added to enhance the ionic conductivity, as measured by both Electrochemical Impedance Spectroscopy (EIS) and by the slope of DC current/voltage curves. Successful separation and collection of the hydrogen and oxygen gas was inferred from the ratio of 2:1 in the volumes of hydrogen and oxygen collected. Both acid and alkali treatments were trialled and it was found that, whereas acid treatment flocculated the mud, adding NaOH increased the dispersion, conductivity and viscosity, and reduced clogging. The conductivity of both the 24% dry mass alkali mud and a control 4% dry mass alkali bentonite suspension increased to that of pure NaOH 1 M when repeatedly electrolysed. Hydrogen and oxygen gas was collected for 10% and 24% dry mass muds. The less viscous 10% dry mass mud showed turbulent liquid-like behaviour which led to gas mixing but the 24% mud showed stable, solid-like flow and reliable gas separation. Three components of the energy efficiency of the electrolysis process are reported and discussed – the voltage efficiency of 42%, a gas collection efficiency of 50% and the auxiliary power efficiency of 60%. The overall energy efficiency due to these three contributing efficiencies, was 13% of the Higher Heating Value of 142 MJ/kg H2 for a current density of 45 mA/cm2. This mud electrolyser may still be considered worth developing for an off-grid, low budget site with a low-power source of renewable energy.